Effect of GA3, Waxing and Micro Perforated Bags on shelf Life and Selected Quality Attributes of Papaya Fruit - Mesfin G, Biniam; Bower, J P (Journal of Postharvest Technology, 2017)
Papaya fruit is characterized by a relatively short shelf-life. To extend the shelf-life and to investigate the effect of various postharvest treatments on shelf-life and quality, a study was conducted on papaya (Carica papaya) cv. Hortus Gold. The treatments included gibberellic acid (GA3), waxing and micro-perforated bags (MPB). Fruits were held at four different temperatures (5.5, 7, 10 or 22ºC). Percentage weight loss (PWL), firmness, skin colour change and respiration rate were evaluated on a weekly basis during the storage period. Selected quality attributes such as total soluble solids (TSS), titratable acids (TA), pH and sugar:acid ratio were also measured after storage. Based on the colour change and softening days to ripen was determined. PWL, softening, yellowing and respiration rate increased irrespective of treatments as the storage time and temperature was increased. MPB and waxing significantly (P<0.001) reduced PWL and softening compared to the control fruits. This was consistent for all storage temperatures. GA3 resulted in significantly lower (P<0.001) PWL compared to the control at 7, 10 and 22ºC, but not at 5.5ºC. Moreover, waxing and GA3 treatments significantly reduced colour development and the respiration rate at all storage temperatures. An increased respiration rate was evident in MPB at 5.5 and 22ºC. Fruits at 7 and 10ºC exhibited an increased shelf-life up to eight and six weeks, respectively, while fruits at 5.5ºC showed chilling injury, which resulted in an increase in respiration rate and PWL. Similarly, fruits at 22ºC showed a rapid respiratory climacteric after two weeks of storage and deteriorated very rapidly. There was no measurable difference among treatments in their TSS, TA, pH and sugar:acid ratio at all storage temperatures. Waxing, GA3 and MPB are, therefore, promising means of controlling papaya postharvest loss and, hence, increase shelf-life with no significant effect to the quality within the conditions of poor infrastructure and poor storage facilities.